Randomized controlled trial for selective preventive transdiagnostic intervention for adolescents at risk for emotional disorders - Manuel Vivas-Fernandez; Luis-Joaquin; Jose A. Piqueras; Jose-Antonio; Josefa Canals-Sans; Lourdes Espinosa-Fernandez; David Jimenez-Vazquez; Maria del Mar Diaz-Castela; Paula Morales-Hidalgo; Maria Rivera; Jill Ehrenreich-May (BMC, 2023)
Abstract Significant evidence does exist on the effectiveness of transdiagnostic interventions to improve emotional problems in clinical populations, and their application as universal and indicated prevention programs. However, no randomized controlled trials (RCT) studying selective transdiagnostic prevention intervention have been published. This is the first known RCT to evaluate the efficacy/effectiveness of an evidence-based selective prevention transdiagnostic program for emotional problems in adolescents. The impact of three different interventions was evaluated: (1) PROCARE (Preventive transdiagnostic intervention for Adolescents at Risk for Emotional disorders), which is a group-based, abbreviated version of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Adolescents (UP-A), along with adding a booster session to reduce risk of onset of anxiety and depression, (2) PROCARE + , which includes the PROCARE protocol along with personalized add-on modules tailored to match adolescents' risk factors, and (3) an active control condition (ACC) based on emotional psychoeducation. In total, 208 adolescents (48.5% girls) evidencing high risk and low protective factors were randomized and allocated to PROCARE, PROCARE + or ACC. Data from 153 adolescents who completed all assessments in the different phases of the study were analyzed. Self- and parent-reported measures were taken at baseline, as well as after the intervention, a 6 month follow-up was carried out, together with a 1 month follow-up after the booster session. Differences between conditions were significant on most of the outcome measures, with superior effect sizes for PROCARE + in the short and long term. Interventions were acceptable in terms of acceptability, with good satisfaction rates. Tailored targeted selective transdiagnostic interventions focused on mitigating risk factors and promoting protective factors in vulnerable adolescents are promising.